THE IMPLEMENTATION OF NOTE-TAKING PAIRS TECHNIQUE IN TEACHING READING COMPREHENSION - ., Aisyah .; Anisah, Ani Wahyu (Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
ABSTRACT The aims of this research are to find out whether the implementation of Note-Taking Pairs technique effective in teaching reading comprehension at junior high school. The method used in the research is quantitative method and the design is quasi-experimental design. The sampling technique used in this research was random sampling. Two classes were taken as the subject namely experimental and control class. The data of test got from both experimental and control class was analyzed by T-test formula. The result of calculation showed that taccount was 6.58, and ttable with df 75 in the significant degree of 5% is 1.992. It means that taccount is higher than ttable (6.58 > 1.992). The average of post-test in the experimental class was 81, while the KKM of English subject is 75. It can be concluded that Note-Taking Pairs Technique is effective in teaching reading comprehension at junior high school. Keywords: Note-Taking Pairs Technique, Reading comprehension, studentsâ response